167k views
3 votes
Find the solution to the following equations

2x-y=-3
x+y=0


(0,0)
(-1,1)
(1,-1)

2 Answers

2 votes
The answer is (x,y) (-1,1) because x+y=0 3x?=-3, x is -1 so -1+y=0 y is 1 so -1+1=0 2x (-1)-1=-3 -3= -3 0 = 0
User Bozic Nebojsa
by
5.5k points
3 votes

Answer: The correct option is (B) (-1, 1).

Step-by-step explanation: We are given to find the solution to the following system of equations :


2x-y=-3~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)\\\\x+y=0~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(ii)

We will be using the method of Elimination to solve the given system.

Adding equations (i) and (ii), we get


(2x-y)+(x+y)=-3+0\\\\\Rightarrow 3x=-3\\\\\Rightarrow x=-(3)/(3)\\\\\Rightarrow x=-1.

From equation (ii), we get


-1+y=0\\\\\Rightarrow y=1.

Therefore, the required solution is (x, y) = (-1, 1).

Thus, option (B) is CORRECT.

User Omkesh Sajjanwar
by
5.2k points